Increasing Fire Weather Season Overlap Between North America and Australia Challenges Firefighting Cooperation - Doug Richardson; Andreia F. S. Ribeiro; Fulden Batibeniz; Yann Quilcaille; Andrea S. Taschetto; Andrew J. Pitman; Jakob Zscheischler (Earth's Future)
Abstract The USA, Canada and Australia are members of an international partnership that shares firefighting resources, including equipment and personnel. This partnership is effective because fire risk between Australia and North America is historically asynchronous. However, climate change is causing longer fire seasons in both regions, increasing the likelihood of simultaneous fire risk and threatening the partnership's viability. We focus on spatially compounding fire weather as the annual number of days on which the fire seasons in Australia and North America overlap, investigating historical and future projections of fire weather season lengths. We use the Canadian Fire Weather Index and compute season length statistics using ERA5 reanalysis data together with historical and future projections from four CMIP6 single model initial‐condition large ensembles. Our analysis shows that the length of fire weather season overlap between eastern Australia and western North America has increased by approximately one day per year since 1979. The interannual variability of overlap is driven primarily by the variability in Australia, with correlations between that region's fire weather season length and the degree of overlap exceeding 0.9. Composites of ERA5 and CMIP6 sea surface temperatures suggest a link between the interannual variability of overlap and the El Niño‐Southern Oscillation, despite this climate mode's opposing relationship with fire weather in the two regions. Finally, we find that the overlap is projected to increase by ∼4 to ∼29 days annually by 2050. We conclude that an increasing overlap of fire seasons is expected to constrain current resource‐sharing agreements and shorten preparedness windows.